Enhancing Teacher-Students Interaction in Urban and Rural Schools in Pekalongan - Handayani, Indah; Zulfa Sakhiyya; Abdurrahman Faridi (English Education Journal, 2023)
Urban and rural contexts often present different challenges and dynamics in education. There is a gap in terms of infrastructure, resources, teacher training and student backgrounds between urban and rural schools. The research focuses on understanding the differences and similarities in teacher-student interactions between urban and rural schools in Pekalongan, Indonesia. The research uses a qualitative approach and employs the SETT framework proposed by Walsh (2006) for data analysis. Two schools, one from an urban setting and another from a rural setting in Pekalongan, were selected as the research settings. The findings indicate that all four classroom modes (managerial, material, skill and system, and classroom context) are present in both urban and rural school lesson. Teachers in both settings engage in various interactional features. However, the use of interactional features in urban school needs to be improve to enhance student engagement. The study's significance lies in providing valuable insights for educators, policymakers, and curriculum developers in Pekalongan and similar settings. It highlights the importance of teacher-student interactions in improving English language learning experiences and outcomes for students. By addressing the disparities in education quality between urban and rural contexts, this research can contribute to enhancing the overall quality of education in both settings. In summary, this research sheds light on the crucial role of teacher-student interactions in urban and rural schools, offering a pathway to address educational disparities and improve learning experiences for students in Pekalongan and similar environments.